Mineralization of Western Cape rivers : an investigation into the deteriorating water quality related to drainage from cultivated lands along selected catchments, with special reference to the Great Berg River - Fourie, Jacobus Martin (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. Agric.) -- University of Stellenbosch, 1976.